Optimization of Ca/Si ratio in schists to enhance the pozzolanic supplementary cementitious material for OPC blending - Pozhhan Mokhtari; Kosar Hassannezhad; Zeynep Basaran Bundur; Sezen Donmez; Mehmet Ali Gulgun; Waltraud M. Kriven (International Journal of Ceramic Engineering & Science, 2024)
Abstract Supplementary cementitious materials (SCMs) are partial substitutes for ordinary Portland cement (OPC) to reduce cost, the production of carbon dioxide (CO2), and fossil fuel consumption. Recent studies illustrated the effectiveness of calcined kaolinite clay as a proper partial replacement for OPC. Hence, schist‐type materials containing sufficient clay contents are regarded as promising candidates for OPC replacement. This study focuses on the possible use of activated calcium carbonates (CaCO3) to augment pozzolanic reactions of schists as a substitute for OPC. The use of activated calcium carbonates proved to be successful in expediting pozzolanic reactions and facilitating the formation of additional calcium aluminosilicate hydrate (C‐A‐S‐H). In this study, the optimal strength performance for blended cement was achieved by adjusting the total carbonate content to 30 wt.% of the schist. The decision to introduce carbonate to the schist was guided by calculations determining the need for an excess of calcium ions to fully harness the potential for C‐A‐S‐H formation. Virgin and augmented schists were activated by up to 80% of their respective potentials by heat treatment. Phase content and decomposition behavior of the active components were investigated by thermogravimetric analysis (TGA), x‐ray diffraction (XRD), and scanning electron microscopy (SEM). Cement paste samples incorporating 30 wt.% replacement of OPC with activated schist SCMs were prepared. The phase distribution and compressive strengths of these samples were assessed at hydration intervals of 2, 7, 28, 50, and 90 days. Cement formulations with activated calcium‐augmented SCMs exhibited compressive strength values at 109%, 101%, 96%, 95%, and 94% compared to pure cement paste at 2, 7, 28, 50, and 90 days, respectively. These values surpassed 90% of the compressive strength of pure OPC at equivalent hydration time points.